Maintenance of Certification: Update on Attitudes of Members of the American Society of Neuroradiology - Yousem, D.M.; Nidecker, A. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Neuroradiology is in the fifth year of subspecialty recertification. New requirements for the MOC process include a PQI initiative. The purpose of this report was to survey compliance of ASNR members with the MOC process. MATERIALS AND METHODS: A 12-question Internet-based survey was sent to the 2864 members of the ASNR through e-mail addresses. The survey asked questions regarding compliance with cognitive testing, SAMs, CME credits, and PQI. Multiple reminders were sent and open comments graded for attitudes toward the MOC process. RESULTS: While most respondents were engaged in the MOC process (878/1074 [81.8%]) and were aware of CME and SAMs, (736/1067 [69%]) and cognitive testing requirements of the recertification, the PQI initiative had limited participation and many questions about the component. Of the 1057 respondents, 687 (490 not started, 87 registered but not started, 110 unaware of PQI) or 65% had not started a PQI project at the time of the survey. The ASNR was asked to help with the cognitive examination by 25 (4.4%), CME offerings by 53 (9.4%), SAM modules by 88 (14.0%), and PQI projects by 205 (36.2%) respondents. Open comments were generally unfavorable toward the MOC-PQI process by a 3:1 ratio. CONCLUSIONS: Compliance with the MOC process has improved since a prior survey 3 years ago; however, confusion over the PQI process remains the primary concern of ASNR members. ABMSAmerican Board of Medical SpecialtiesABRAmerican Board of RadiologyASNRAmerican Society of NeuroradiologyCAQCertification of Added QualificationCMEcontinuing medical educationMOCmaintenance of certificationPQIpractice quality improvementRSNARadiological Society of North AmericaSAMself-assessment module